Factors Associated with the Implementation of Food Hygiene and Sanitation in Restaurants - Adillah, Anisah; Ulva, Fadillah; Ilmaskal, Radian (STIKes Alifah Padang, 2023)
The food management facilities in Padang had not yet reached the target achievement of an 87% food hygiene and sanitation rate; they had only reached 72%. The food management facilities in the Pauh Primary Health Care working area were the lowest in food hygiene and sanitation standards in Padang. Contamination in food and beverages could become a means of disease transmission, one of which was through food handlers. The aim of this study was to determine the factors associated with the implementation of food hygiene and sanitation in restaurants within the Pauh Primary Health Care working area in Padang. This research was of a quantitative study with an analytical approach and a cross-sectional study design. The study was conducted from March to July 2023. The research population consisted of all 230 food handlers. A sample of 87 food handlers was taken using the accidental sampling technique, utilizing questionnaires and observation sheets. Data analysis was carried out using univariate and bivariate analysis. The research findings showed that 48.3% of food handlers had a poor implementation of food hygiene and sanitation, 49.4% had low levels of knowledge, 49.4% had inadequate sanitation facilities, and 70.1% were poorly supervised by sanitation personnel. Based on bivariate analysis, there was a significant relationship between the availability of sanitation facilities (p=0.001) and the supervision of sanitation personnel (p=0.000) with the implementation of food hygiene and sanitation. Additionally, there was no relationship between the level of knowledge and the implementation of food hygiene and sanitation (p=0.589). The implementation of food hygiene and sanitation was influenced by several factors, namely the availability of sanitation facilities and the supervision of sanitation personnel. It was recommended for food handlers to practice personal hygiene, for restaurant owners to provide adequate sanitation facilities, and for the Pauh Primary Health Care to enhance supervision and increase awareness about food hygiene and sanitation.